2014
DOI: 10.1086/675985
|View full text |Cite
|
Sign up to set email alerts
|

Gas Exchange and Pulmonary Hypertension following Acute Pulmonary Thromboembolism: Has the Emperor Got Some New Clothes Yet?

Abstract: Patients present with a wide range of hypoxemia after acute pulmonary thromboembolism (APTE). Recent studies using fluorescent microspheres demonstrated that the scattering of regional blood flows after APTE, created by the embolic obstruction unique in each patient, significantly worsened regional ventilation/ perfusion (V/Q) heterogeneity and explained the variability in gas exchange. Furthermore, earlier investigators suggested the roles of released vasoactive mediators in affecting pulmonary hypertension a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 168 publications
(300 reference statements)
0
12
0
3
Order By: Relevance
“…We believe that the most likely explanation entails heterogeneity in ventilation/perfusion (V/Q) relationships throughout the different regions of the lung, with low V/Q ratio lung units existing in some areas 14,15 and high V/Q relationships in others. 16 Under these circumstances, positional changes in blood flow distribution during sleep may lead to increased flow through low V/Q lung regions and subsequent hypoxia while supine. We found that T90 was associated with markers of PH severity (mPAP and PVR).…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the most likely explanation entails heterogeneity in ventilation/perfusion (V/Q) relationships throughout the different regions of the lung, with low V/Q ratio lung units existing in some areas 14,15 and high V/Q relationships in others. 16 Under these circumstances, positional changes in blood flow distribution during sleep may lead to increased flow through low V/Q lung regions and subsequent hypoxia while supine. We found that T90 was associated with markers of PH severity (mPAP and PVR).…”
Section: Discussionmentioning
confidence: 99%
“…Even if a greater number of pigs had shown a significant lower number of atelectasis in the group with retrograde perfusion, this may indicate the worsening of microatelectasis because of the one hour of no flow in the pulmonary vessels in the antegrade group, thus suggesting it as a beneficial effect of retrograde perfusion. It has been debated that a PE in itself may provoke atelectasis as a way of helping to restore the disequilibrium in the ventilation-perfusion ratio in the lungs, most likely mediated by a low CO 2 in the obstructed vessels in the lungs [11][12][13]. Further research is needed to verify this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The respiratory distress could be caused by pulmonary artery thrombosis and mild pulmonary edema. Adult respiratory distress syndrome (ARDS), or non-cardiogenic pulmonary oedema and hypoxia could be associated with pulmonary thromboembolism [29]. Furthermore there is a possibility of Hepatopulmonary syndrome (HPS) in this patient.…”
Section: B: Sinusoidal Dilatation and Congestion (Magnification ×400) C: Cellular Swelling (Hydropic Degeneration) Of Hepatocytes As Enlamentioning
confidence: 94%